2010
DOI: 10.1016/j.cell.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Essential Regulation of Cell Bioenergetics by Constitutive InsP3 Receptor Ca2+ Transfer to Mitochondria

Abstract: Mechanisms that regulate cellular metabolism are a fundamental requirement of all cells. Most eukaryotic cells rely on aerobic mitochondrial metabolism to generate ATP. Nevertheless, regulation of mitochondrial activity is incompletely understood. Here we identified an unexpected and essential role for constitutive InsP3R-mediated Ca2+ release in maintaining cellular bioenergetics. Macroautophagy provides eukaryotes with an adaptive response to nutrient deprivation that prolongs survival. Constitutive InsP3R C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

62
947
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 917 publications
(1,017 citation statements)
references
References 51 publications
62
947
6
2
Order By: Relevance
“…As previously reported, an impairment of mitochondrial Ca 2+ handling is associated with mitochondrial diseases. 35 Recently, Cardenas et al 6 reported that constitutively Ca 2+ release from the ER controls cellular bioenergetics and autophagy. Based on these observations, we investigated cellular Ca 2+ Figure S3d) and in permeabilized cells, where the contribution of plasma membrane or ER channels to the mitochondrial Ca 2+ response is absent (Supplementary Figure S3c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As previously reported, an impairment of mitochondrial Ca 2+ handling is associated with mitochondrial diseases. 35 Recently, Cardenas et al 6 reported that constitutively Ca 2+ release from the ER controls cellular bioenergetics and autophagy. Based on these observations, we investigated cellular Ca 2+ Figure S3d) and in permeabilized cells, where the contribution of plasma membrane or ER channels to the mitochondrial Ca 2+ response is absent (Supplementary Figure S3c).…”
Section: Resultsmentioning
confidence: 99%
“…6,39,40 Western blotting analysis of AMPK phosphorylation on Ser172 (p-AMPK) 40 revealed low p-AMPK level in resting conditions in control cells. Conversely, all patient-derived fibroblasts displayed a slight increase in p-AMPK levels, as expected in cells with deficiency of the respiratory chain complexes, but in Pat#1 this increase was dramatic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations